Dostoevsky on Twitter: Twitterfiction as a Learning Tool in SLA - A.S. Bovshik (Язык и текст, 2020)
The article examines the benefits of twitterfiction, a relatively new form of literary production, as a means of second language acquisition in the context of recreational reading. Pushed forward by the influential American educational researcher Stephen Krashen, free voluntary reading (FVR) has been proven to be an extremely powerful factor in developing various aspects of second language competence and getting students committed to reading more. This paper attempts to evaluate both quantitative and qualitative complexity measures of twitterfiction as in the case of TWITTERATURE by Alexander Aciman and Emmett Rensin to better understand the educational potential of the above type of prose. Readability formulas such as the Gunning Fog index and the Coleman-Liau index are deployed to evaluate the structural complexity of the text. ‘Attentive reading’, being a subjective factor in many ways, is a tool we apply to assess the text on the levels of semantics and pragmatics. The research concludes that twitterfiction, as demonstrated in the book, is an adequate ESL supplementary material alongside comics, graphic novels and level 4 graded readers.